Multivariate analysis of cellular immunity state in rhesus-sensitized women - Marichereda, V. G.; Cherniyevskaya, S. G.; Moskalenko, T. Ya.; Shevchenko, I. M.; Shevchenko, N. V. (Journal of Education, Health and Sport, 2018)
Implementation of anti -D prophylaxis significantly reduced the degree of allogenic immunization (AI), while this method of prevention is not universal. According to the data of different authors, about 0.3% of Rh (D) - negative women still become Rh (D) AI. We failed to find data as to the state of cellular immunity (CI) in rhesus-sensitized (Rh-S) pregnancy, as well as the possibility of its indicators use for predicting and diagnosing the pregnancy course in the group of women under study. The objective: to evaluate the state of CI and identify its most diagnostic important components in the cohort of rhesus-sensitized women. Materials and methods. The state of CI (population and subpopulation of lymphocytes) was studied in 82 pregnant women, 37 had Rh-S with different titers of antibodies, control group comprised 45 healthy women without rhesus sensitization. Results: The most significant indicators of Rh-S women's CI were distributed among the three main factorial components. Multivariate analysis method was used. Activated subpopulations of T-lymphocytes and T-killers comprised Factor 1. Factor 2 is represented by indices of the lymphocyte population - B-lymphocytes (CD19 +) with a direct correlation of 0.88, as well as T-lymphocytes (CD3 +) with an inverse - 0.92. Factor 3 included the main subpopulations of lymphocytes (T-helpers and T- suppressors), as well as the immunoregulatory index (the coefficient of their ratio). Conclusion. The most significant indicators for CI study in Rh-S women are: CD19 + (B-lymphocytes), CD3 + (T-lymphocytes), CD3 + HLA-DR + (activated T - lymphocytes), CD3 + CD4 + HLA-DR + ( activated T -helpers), CD3 + CD8 + HLA-DR + (activated T-suppressors), NK-cells CD3-CD16 / 56 + (T-killers) and immunoregulatory index CD3 + CD4 + / CD3 + CD8 +.